Fetal alcohol exposure and development of the integument - Longhurst WD; Ernst J; Burd L (Dove Medical Press, 2016)
William D Longhurst,1 Jordan Ernst,2 Larry Burd3 1Center for Emergency Medicine, University Hospitals Case Medical Center, Case Western Reserve University, Cleveland, OH, USA; 2University of North Dakota School of Medicine and Health Sciences, Grand Forks, ND, USA; 3Department of Pediatrics, North Dakota Fetal Alcohol Syndrome Center, University of North Dakota School of Medicine and Health Sciences, Grand Forks, ND, USA Background: The physiology of fetal alcohol exposure changes across gestation. Early in pregnancy placental, fetal, and amniotic fluid concentrations of alcohol exposure are equivalent. Beginning in mid-pregnancy, the maturing fetal epidermis adds keratins which decrease permeability resulting in development of a barrier between fetal circulation and the amniotic fluid. Barrier function development is essential for viability in late pregnancy and in the extra-uterine environment. In this paper we provide a selected review of the effects of barrier function on fetal alcohol exposure. Methods: We utilized a search of PubMed and Google for all years in all languages for MeSH on Demand terms: alcohol drinking, amnion, amniotic fluid, epidermis, ethanol, female, fetal development, fetus, humans, keratins, permeability, and pregnancy. We also reviewed the reference lists of relevant papers and hand-searched reference lists of textbooks for additional references. Results: By 30 gestational weeks, development of barrier function alters the pathophysiology of ethanol dispersion between the fetus and amniotic fluid. Firstly, increases in the effectiveness of barrier function decreases the rate of diffusion of alcohol from fetal circulation across fetal skin into the amniotic fluid. This reduces the volume of alcohol entering the amniotic fluid. Secondly, barrier function increases the duration of fetal exposure by decreasing the rate of alcohol diffusion from amniotic fluid back into fetal circulation. Ethanol is then transported into maternal circulation for metabolism or elimination. Conclusion: In late pregnancy, barrier function modifies alcohol diffusion rates across the epidermis back into fetal circulation. This increases the duration of exposure from each episode of drinking. This information may be useful for clinicians who care for women with alcohol use disorders during pregnancy, and may also be useful in explaining the rationale for avoiding alcohol use throughout pregnancy, including late pregnancy. Keywords: fetal, exposure, ethanol, integument, fetal alcohol spectrum disorders, amniotic fluid, alcohol